QUALITY OF LIFE PERSPECTIVE CORRELATION IN CHILDREN UNDERGOING AMBLYOPIA OCCLUSION THERAPY AND THEIR PARENTS AS PROXY: Oral Presentation - Experimental Study - Resident - ANDIVAN RAHMAN; MAYASARI WAHYU KUNTORINI; NINA RATNANINGSIH; FETI KARFIATI MEMED; IRAWATI IRFANI; PRIMAWITA OKTARIMA AMIRUDDIN; SESY CAESARYA (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : One of the main therapies used to treat amblyopia in the dominant eye is occlusion therapy. When used on the dominant eye during activities, eye patches can lead to quality of life issues include visual, cosmetic, and psychosocial disorders. To improve visual acuity in the suppressed eye and stop a progressive loss of visual acuity, therapy must be followed. An important factor affecting a child's compliance with occlusion therapy is parental support. Parental negativity affects children's level of support, and as a result, a decreased compliance. This research aimed to determine the relationship between quality of life and the perspectives of parents and children receiving occlusion therapy. Methods : This is a correlation study with a cross-sectional design. Fifty-one subjects were addressed in the amblyopia children's group and fifty-one subjects in the parents’ group. Every participant was directly interviewed. Correlation analysis was used to assess the relationship between the results of interviews with children and their parents. Results : There is a decrease in the quality of life in children undergoing therapy, both from the perspective of the child and their parents. The decline in the quality of life that occurs in children is not as low as parents think. The results of the questionnaires for the children and their parents in total demonstrated a significant correlation (p = 0.0001) and a moderately positive correlation (R = 0.598). Conclusion : There is a positive correlation between children and parents in assessing the quality of life due to occlusion therapy.